Analysis of the Cu-Al Milling Stages Through the Microstructure Evolution Studied by TEM and SEM - Giordana, María Florencia (2017)
Mechanical alloying of Cu-16 at.%Al and Cu-30 at.%Al was performed using both a planetary and a horizontal milling devices. The starting powders were high-purity Cu and Al. The different stages of milling were identified and characterized as initial, intermediate, final, and completion. The obtained microstructures were investigated by scanning electron microscopy and transmission electron microscopy. The evolution of the microstructure was studied considering the particle size variation. A decrease in the particle size was found as the Al content increases. The evolution of the nanostructure was studied considering the grain size variation. No marked changes on the nanostructure were detected during milling regardless either the type of mill used or composition selected. Mean grain sizes’ values found were between 10 nm and 26 nm for each stage of milling. Power consumption of the milling process was calculated at laboratory scale to analyze the chances of a potential scaling up of the milling process. Starting aggregation state, microstructure and dominant phase changes, and evolution of mechanical alloying stages were considered. Performance of milling was compared to traditional high-temperature methods to compare the advantages and disadvantages of both synthesis methods.